Soil microbial diversity during 30 years of grassland restoration on the Loess Plateau, China: Tight linkages with plant diversity. (11th April 2019) - Guo, Yanqing; Hou, Lijun; Zhang, Zhiying; Zhang, Jianli; Cheng, Jimin; Wei, Gehong; Lin, Yanbing
Abstract: Restoring ecosystems has been a key strategy to combat land degradation and reverse losses in biodiversity. Because interactions between communities above and below the ground drive key ecosystem processes, they can profoundly influence ecological succession trajectories. However, relatively little empirical information is available for plant–microbial diversity linkages during ecological restoration. Here, using the Illumina platform for bacterial and fungal sequencing, we investigated linkages between soil microbial and plant diversity across a 30‐year chronosequence of restored grasslands on the Loess Plateau in Northwestern China. The results showed that plant, bacterial, and fungal species richness all increased with increased years of grassland restoration, during which their community compositions shifted among six different habitats. The microbial community assembly data were integrated into a co‐occurrence network analysis, revealing greater network complexity in the late restoration stage (25 and 30 years). The alpha and beta diversities of both the bacterial and fungal communities were significantly and positively correlated with plant communities. Bacterial community composition was governed primarily by soil edaphic factors and deterministic processes, whereas fungal community composition was structured mainly by plant community composition and both deterministic and stochastic processes. This evidence strongly suggests that different ecological processes shaped bacterial and fungal communities during ecological restoration of the grasslands. Our results provide insight into the aboveground–belowground associations of restored habitats, which may have implications for ecological restoration practices and biodiversity maintenance in arid and semiarid grassland ecosystems.